Treatment of basal cell cancer in the periorbital area using a pulsed copper vapour laser - S. V. Klyuchareva; I. V. Ponomarev; S. B. Topchy; A. E. Pushkareva; Yu. N. Andrusenko (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
An increase in life expectancy in developed countries is inevitably accompanied by an increase in the number of nonmelanoma skin diseases, which are primarily represented by basal cell cancer (BCC) occurring in elderly and old-age patients. The pathogenesis of such diseases is associated both with impaired proliferation and differentiation of the keratinocytes of the epidermal basal layer, as well as with the transformation of the vasculature in the papillary dermis in the vicinity of BCC. In recent years, such conditions have been increasingly treated using CO2 , neodymium, diode and pulsed-dye lasers. In many cases, these devices allow malignant BCC cells to be successfully eliminated. However, the use of near-infrared lasers in the periorbital area is limited due to a higher risk of damaging the organs of the visual system. Therefore, a search for new laser surgery methods that can be used for treating malignant skin tumours seems to be a prospective research direction.Methods. 3 male and 9 female patients diagnosed with primary BCC were treated using a copper vapour laser (Yakhroma-Med). The age of the patients varied from 34 to 77 years. Laser treatment was carried out in one session under the following irradiation parameters: the wavelength of 511 and 578 nm, the average power of up to 3 W and a series of 15 ns pulses. The pause between the pulses was 60 μs, with the exposure time ranging from 200 to 600 ms. The light spot diameter on the skin surface was 1 mm. The follow-up monitoring duration was 24 months.Results. In all the BCC patients, one session of copper vapour laser treatment allowed malignant cells in the disease area to be completely eliminated without relapses during 2 years after the therapy. The duration of skin healing in the irradiated area was 2 weeks in patients under the age of 40 years, compared to 3-4 weeks in elderly patients. After the treatment, short-term side effects, such as a slight edema, erythema and peeling, were observed.